(untitled) (Journal of the College of Basic Education, 2022)
The study was divided between a first illumination pertaining to the poet and a second one pertaining to his poetic text. The first axis included a study of the poet’s life, beginning with the study of his name and surname, then shedding light on the most important features of his personality, and the nature of his relationship with Abd al-Malik ibn Marwan, ending with determining his position among the poets of his time.While the second axis was devoted to analyzing the poem and revealing its characteristics and advantages, revealing its substantive links, intellectual bridges, and its emotional unity that directed the transitions between its paintings.These axes were preceded by a quick review of the methods and theories of literary criticism and what came of it in their applied field. The methodology of the study was determined, then I came to a brief description of the poem of Umayyad contradictions, and the results were deposited in a conclusion, which was followed by proof of approved sources and references.